Comparative study of methods to evaluate depth of cure of restorative composites - Romano, Beatriz; Giannini, Marcelo; Soto, Jorge; Mendonça, Beatriz de; Price, Richard (Revista dos Trabalhos de Iniciação Científica da UNICAMP, 2019)
The objective of this study was to compare two methods to evaluate the depth of cure (DOC) of restorative composites and if the extension of the light-activation time would increase the DOC of composites.Two bulk-fill composites (Tetric Evoceram Bulk Fill, Ivoclar Vivadent and Filtek One Bulk Fill, 3M Oral Care) and two conventional composites (Tetric N-Ceram, Ivoclar Vivadent e Filtek Z350 XT, 3M Oral Care) were tested. Cylindrical samples were made by inserting the composites into a hole of matriz with 5 mm internal diameter and 13 mm depth, and light-activated with light curing unit from the same manufacturers of each composite, using the manufacturer recommendation time (MRT), or for double the time (DOT). Two methods compared were: 1- ISO 4049 test and 2- dissolution with organic solvent (acetone). For the ISO 4049 test, the unpolymerized resin was manually removed with a plastic spatula and the length of the samples measured with a digital caliper to calculate the DOC. In the organic solvent method, the unpolymerized resin was removed manually and samples were immersed inn the dark in acetone for 48 hours for DOC measurement. It was observed that light curing for DOT produced significantly higher DOC than those for MRT. Differences in DOC measurements between ISO and "organic solvent" methods were material dependent.